Barcelona scale for buccophonatory apraxia: Quantitative assessment tool - N. Montagut; S. Borrego-Écija; J. Herrero; A. Lladó; M. Balasa; E. Muñoz; F. Valldeoriola; R. Sánchez-Valle (Neurología (English Edition))
Introduction: Currently there is no tool to quantify buccophonatory apraxia to stratify, compare and monitor patients longitudinally in an objective manner. Our aim in this study is to create a quantitative scale for buccophonatory apraxia and evaluate it in patients with the non-fluent/grammatical variant of primary progressive aphasia (nfvPPA) and other neurodegenerative diseases that occur with speech and/or language problems. Methods: The scale was designed based on useful elements in the assessment of buccophonatory apraxia and the total was quantified in seconds. The scale was administered to 64 participants with diagnoses of: nfvPPA, semantic variant of primary progressive aphasia (svPPA), logopenic variant of primary progressive aphasia (lvPPA), Huntington’s disease, Parkinson’s disease, as well as a group of healthy controls. Results: Patients showed a significantly higher score compared to controls. The nfvPPA group had the highest mean score on the scale (429 seconds ± 278). The scale was useful to differentiate vnfPPA from svPPA and Parkinson’s disease (area under curve [AUC] of 0.956 and 0.989, respectively), but less to differentiate it from Huntington’s disease (AUC = 0.67) and lvPPA. There was a statistically significant relationship between total score and disease severity in nfvPPA (P < .029). Conclusions: The Barcelona scale for buccophonatory apraxia could be useful to quantitatively evaluate buccophonatory apraxia in different neurodegenerative diseases, and compare patients, especially in nfvPPA. Resumen: Introducción: Actualmente no existe una herramienta que permita cuantificar la apraxia bucofonatoria para estratificar, comparar y monitorizar longitudinalmente a los pacientes de manera objetiva. Nuestro objetivo en el presente trabajo es crear una escala cuantitativa para la apraxia bucofonatoria y evaluarla en pacientes con la variante no fluente/agramatical de la Afasia Progresiva Primaria (vnfAPP) y otras enfermedades neurodegenerativas que cursan con problemas del habla y/o lenguaje. Métodos: Se diseñó una escala a partir de elementos útiles en la exploración de la apraxia bucofonatoria y se cuantificó el total en segundos. Se administró la escala a 64 participantes con diagnósticos de: vnfAPP, variante semántica de la Afasia Progresiva Primaria (vsAPP), variante logopénica de la Afasia Progresiva Primaria (vlAPP), enfermedad de Huntington, enfermedad de Parkinson, así como a un grupo de controles sanos. Resultados: Los pacientes mostraron una puntuación significativamente mayor respecto a los controles. El grupo de vnfAPP presentó la puntuación media más alta en la escala (429 segundos ± 278). La escala resultó útil para diferenciar la vnfAPP de la vsAPP y de la enfermedad de Parkinson (área bajo la curva [AUC] de 0.956 y 0.989 respectivamente), pero menos para diferenciarla de la enfermedad de Huntington (AUC = 0.67) y de la vlAPP (AUC = 0.772). Existió una relación estadísticamente significativa entre la puntuación total y la gravedad de la enfermedad en la vnfAPP (P < .029). Conclusiones: La escala Barcelona para la apraxia bucofonatoria podría ser útil para evaluar cuantitativamente la apraxia bucofonatoria en diferentes enfermedades neurodegenerativas, y comparar pacientes, en especial en la vnfAPP.